Oil Palm Kernel Shell-derived Graphene Derivative Anode Electrodes: Characterizations And Application In Microbial Fuel Cell - Omenesa, Idris Mustapha (2024)
Microbial fuel cell (MFC) has attracted much interest in the bioelectrochemical field as a technique that produces electricity and at the same time removes pollutants from wastewater. However, their abilities to transport electrons is a major barrier in developing the technique to an industrial scale level. The anode material has been highlighted as a critical component of the MFC that needs to be enhanced to address the low electron transportation rate issue. In this study, palm kernel shell (PKS) waste was successfully employed to fabricate the anode electrodes for MFC applications. PKS waste was utilised to synthesise graphene oxide (GO), and reduced graphene oxide (rGO) was prepared from the synthesised GO, which are referred to as PKS-GO and PKS-rGO, respectively. Later, the PKS-rGO was combined with ZnO and TiO2 to generate the composite materials of PKS-rGO/ZnO and PKS-rGO/TiO2, respectively. Several characterization techniques have been used to confirm the successful synthesis of materials for anode production. These fabricated anodes were then evaluated in an MFC to determine power generation performance along with formaldehyde (FA) and naphthalene biodegradation potential. A commercial graphite anode (CGr) has been used in the MFC that serves as a reference to compare the performance of the fabricated anodes. The PKS-rGO/ZnO composite anode showed the highest performance potential in this study.